Problems of Online Learning during Covid-19 Pandemic in EFL Classroom and the Solution - Leli Efriana (JELITA, 2021)
This literature study aims at analyzing online learning difficulties faced by EFL teachers and students, and students’ parents during the Covid-19 pandemic and solutions to solve them. Research data sources are collected through textbooks in print or online form, articles from periodical journal websites, law regulations, and other sources which are relevant to the research problem. The data was analyzed qualitatively with an interactive model, covering data collection, data reduction, data presentation, and conclusions. The implementation of the online learning during the Covid-19 pandemic, especially in EFL learning, caused various problems for teachers, students, and parents, as indicated in the current study.